Trachoma in Northern Ghana: A need for further studies - Gyasi, M.E.; Nsiire, A.; Yayemain, D.; Debrah, O.A.; Asamani, D.; Gyapong, J.; Amoaku, W.M.K. (My University, 2010)
Background: The northern Ghana Upper East Region [UER], Upper West Region [UWR], and Northern Region (NR) lie within the African trachoma belt. The 3 regions share common features of poverty, dryness, dusty environments, and poor environmental hygiene. Trachoma has been identified previously in the NR and the UWR as a disease of public health importance and a control program is underway. Purpose: To establish baseline prevalence and risk factor parameters in the Upper East for possible control of trachoma in the region. Methods: Population-based cross-sectional survey using multi-staged cluster sampling techniques was used. In all 26,323 participants from 4,374 households in 160 communities were examined with a 2.5x magnifying binocular loupe for trachoma; 7,763 were children aged 19 years and 15,191 were aged 15 years and over. Results: Only 3 children were identified with active trachoma (trachoma with follicles, TF=1; trachoma with intense inflammation, TI=2) giving regional prevalence of 0.01% (Confidence Limits, CL: 0.0-0.1) for TF and 0.03% (CL: 0.0-0.1) for TI. Trachomatous trichiasis was measured at 0.05% (CL: 0.0-0.1) while children with clean faces was measured at 95.5%. Only 3.6% of the examined households in the region had access to a toilet facility. Conclusion: Trachoma is not a disease of public health importance in the UER of Ghana despite being in a trachoma endemic zone and sharing the necessary risk factors for the disease. © 2010 Informa Healthcare USA, Inc.
Keywords: EMTREE medical terms: adult; article; child; community; controlled study; cross-sectional study; female; Ghana; groups by age; health survey; household; human; infant; inflammation; male; preschool child; prevalence; priority journal; sample size; school child; trachoma; MeSH: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Epidemiologic Methods; Female; Ghana; Health Surveys; Humans; Infant; Male; Prevalence; Risk Factors; Trachoma; Young Adult